Heinrich Bullinger als Kartäuser? Bullinger als Schüler und Lehrer - Micus, Rosa (Zwingliana, 2019)
The Presider ("Antistes") of the Church of Zurich, Heinrich Bullinger (1531–1575) is considered as accomplished early. Having returned from his formation on the Lower Rhine at the age of 18, he had already turned to the Reformation, after having considered during his studies at Cologne to enter the eremitic order of the Charterhouse. This order was represented with notable houses in Cologne and Bâˆle, and thus notes about the last carthusian at Baˆ le, Thomas Kreß (Kreszi) are transmitted to Bullinger as late as 1545. In Emmerich, Bullinger enjoyed a humanistic education in Latin, which he passed on at a school of Latin instituted specifically for him in the monastery of Kappel in 1523. He held classes in continuous reading of the Bible, as should be the practice at the "Prophezey" instituted 1525 in Zurich, and read the Church Fathers. – Notable in this context is also the abolition of organs in the churches of Zurich from 1524 on for about 80 years; the Carthusians do not know organs in their churches to this day.